(untitled) (Journal of Engineering, 2012)
The present work covers the analytical design process of three dimensional (3-D) hip joint prosthesis with numerical fatigue stress analysis. The analytical generation equations describing the different stem constructive parts (ball, neck, tour, cone, lower ball) have been presented to reform the stem model in a mathematical feature. The generated surface has been introduced to FE solver (Ansys version 11) in order to simulate the induced dynamic stresses and investigate the effect of every design parameter (ball radius, angle of neck, radius of neck, neck ratio, main tour radius, and outer tour radius) on the max. equivalent stresses for hip prosthesis made from titanium alloy. The dynamic loading case has been studied to a stumbling case. The load has been applied on the cap tip as a concentrated load distributed on the interface of ball and socket. The results show that the decreasing of max. Fatigue stress by (175) MPa could be obtained by increasing the outer tour radius from (10)mm to (15) mm and that will change the max. Fatigue zone location from the tour section to the neck. The ball radius and neck angle must be as lower as possible to decrease the fatigue stresses. The most dominate parameter to increase the safety factor is the radius of neck.